Factors influencing the brand credibility of Bank XYZ - Triadi, Tasya Meira; Jahroh, Siti; Taryana, Asep (International Journal Labs, 2024)
As a service provider, Bank XYZ has received numerous complaints from customers. These complaints must be addressed promptly to enhance customer satisfaction. When customers feel that their complaints are acknowledged and resolved, they tend to be more satisfied and trust that the bank can fulfill its promises. This trust leads to customers sharing information and giving recommendations, which positively influences the bank's brand credibility. This study aims to determine the effect of service quality, service recovery, and perceived justice on complaint handling satisfaction, as well as the direct and indirect effects of complaint handling satisfaction through WOM communication. The research sample consists of 250 customers who submitted complaints within the past year, and whose complaints were handled and resolved. Data collection was conducted via Google Forms. Data analysis using SEM-PLS. The fresult of the study indicate that service quality and perceived justice significantly influence complaint handling satisfaction, whereas service recovery does not have a significant impact on complaint handling satisfaction. Furthermore, complaint handling satisfaction has a significant and positive effect on brand credibility, both directly and indirectly through WOM communication. This shows that the higher the level of satisfaction with complaint handling, the greater the customers' trust in Bank XYZ.